Combinatorial Cytokine Code Generates Anti-Viral State in Dendritic Cells - Hartmann, Boris M.; Marjanovic, Nada; Nudelman, German; Moran, Thomas M.; Sealfon, Stuart C. (Frontiers in Immunology, 2014)
The physiological function of the immune system and the response to therapeutic immunomodulators may be sensitive to combinatorial cytokine micro-environments that shape the responses of specific immune cells. Previous work shows that paracrine cytokines released by virus-infected human dendritic cells (DC) can dictate the maturation state of naïve DCs. To understand the effects of paracrine signaling, we systematically studied the effects of combinations cytokines in this complex mixture in generating an antiviral state. After naïve DCs were exposed to either IFNβ or to paracrine signaling released by DCs infected by Newcastle Disease Virus (NDV), microarray analysis revealed a large number of genes that were differently regulated by the DC-secreted paracrine signaling. In order to identify the cytokine mechanisms involved, we identified 20 cytokines secreted by NDV infected DCs for which the corresponding receptor gene is expressed in naïve DCs. By exposing cells to all combinations of 19 cytokines (leave-one-out studies) we identified 5 cytokines (IFNβ, TNFα, IL-1β, TNFSF15 and IL28) as candidates for regulating DC maturation markers. Subsequent experiments identified IFNβ, TNFα and IL1β as the major contributors to this antiviral state. This finding was supported by infection studies in vitro, by T cell activation studies and by in vivo infection studies in mouse. Combination of cytokines can cause response states in DCs that differ from those achieved by the individual cytokines alone. These results suggest that the cytokine microenvironment may act via a combinatorial code to direct the response state of specific immune cells. Further elucidation of this code may provide insight into responses to infection and neoplasia as well as guide the development of combinatorial cytokine immunomodulation for infectious, autoimmune and immunosurveillance-related diseases.